2018
DOI: 10.15177/seefor.18-02
|View full text |Cite
|
Sign up to set email alerts
|

Scotch Pine Regeneration in Magnesite Pollution Conditions in South Ural, Russia

Abstract: Background and Purpose: Technogenic load is considered to be one of the major factors which destabilize forest ecosystems. The impact of chronic aero technogenic pollution near large industrial centers severely affects the plants in these areas; thus, plants cannot fulfill their aesthetic and air-cleaning role. Therefore, many studies have been carried out on technogenic pollution and particularly on magnesite pollution. The aim of the study is to investigate characteristics of the Scotch pine natural regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Research carried out in 2001 showed that the forest cultures planted on ash dumps are characterized by good adaptation and mean increment in height as well as by high preservation (Table 4). and Mohnachev et al (2018) stated that despite the pollution in the technogenic soils, the success of natural regeneration is effected by the stand density and the occurrence of undergrowth of Scots pine. Soil remediation can positively affect the natural regeneration process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research carried out in 2001 showed that the forest cultures planted on ash dumps are characterized by good adaptation and mean increment in height as well as by high preservation (Table 4). and Mohnachev et al (2018) stated that despite the pollution in the technogenic soils, the success of natural regeneration is effected by the stand density and the occurrence of undergrowth of Scots pine. Soil remediation can positively affect the natural regeneration process.…”
Section: Resultsmentioning
confidence: 99%
“…There are about 4.5 million km 2 of man-made landscapes in the world that require radical reclamation (Belyakova et al, 2003). Many studies have been carried out on technogenic pollutions, especially in Russia and the Urals (Zavyalov et al, 2018;Mohnachev et al, 2018;Makhniova et al, 2019;Menshikov et al, 2019;Potapenko et al, 2019). Regretfully, in spite of works significant number on artificial recultivation many problems of their carrying out are still remains to be debated.…”
Section: Introductionmentioning
confidence: 99%
“…INFLUENCE OF SOIL FERTILITY ON THE ABILITY OF SCOTS PINE (Pinus sylvestris L.) TO ADAPT TO TECHNOGENIC POLLUTION are studied for Pinus sylvestris L., Larix sukaczewii Dylis, Betula pendula Roth (ZAVYALOV and MENSCHIKOV, 2016;ZAVYALOV et al, 2018), decrease in elevated biomass of Betula pendula Roth (ZAVYALOV and MENSCHIKOV, 2010), increase in xeromorphy of leaves and Mg in leaves (ZAVYALOV, 2013), weak influence of the pollution on sowing qualities of seeds of Pinus sylvestris L. (MOHNACHEV et al, 2013) and on natural regeneration of Pinus sylvestris L. (MOHNACHEV et al, 2018), but noticeable decrease in radial gain in this tree species (ZAVYALOV, 2018). In the course of work, the zero hypothesis that the fertility of soils is a significant factor for adaptation of the Scots pine to pollution was supported.…”
Section: Resultsmentioning
confidence: 99%
“…A negative effect on generative system development could be caused by (i) overwetting and drought (Velisevich, 2017), (ii) weather conditions in years when the generative structures were initiated and developed (Pukkala et al, 2010), (iii) the sum of positive temperatures during summer in the North of Eurasia (Fedorkov, 2007), (iv) species biological features (Lyanguzova, 2011), and (v) genetic traits of the populations (Hisamoto & Goto, 2017). In addition, many researchers have reported increases in the disturbance of male and female pine generative systems in areas of technogenic pollution (Tretyakova & Noskova, 2004;Kalashnik et al, 2008;Vasilevskaya & Petrova, 2014;Korshikov et al, 2015;Chropenova et al, 2016;Makhniova, 2016;Mohnachev et al, 2016;Makhniova et al, 2017). High levels of heavy metals and other elements might also be a factor in increasing abortive pollen frequency in plants (Reshetova et al, 2015;Chropenova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%